Journey of rheumatoid arthritis patients in Tunisia: From symptoms to treatment - Alia Fazaa,; Hiba Bettaieb,; Meriem Sellami,; Saoussen Miladi,; Kmar Ouenniche,; Leila Souebni,; Selma Kassab,; Selma Chekili,; Leith Zakraoui,; Kaouther Abdelghani,; Ahmed Laatar, (Archives of Rheumatology, 2022)
Objectives: This study aims to assess the different delays of rheumatoid arthritis (RA) patients’ journey from disease onset to treatment initiation and to identify possible influencing factors. Patients and methods: This cross-sectional study included a total of 100 patients (14 males, 86 females; mean age: 56.5±12.4 years; range, 26 to 82 years) who met the 2010 American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) criteria for RA between January 2019 and January 2020. Demographic and clinical data and disease characteristics were collected from the patient interviews and medical files. Five different intervals were defined from symptom onset until the initiation of conventional synthetic disease-modifying anti-rheumatic drugs (csDMARDs). Results: The mean age at RA onset was 46.6±12.4 years. Median delays from onset of symptoms until general practitioner (GP) and rheumatologist consultations were six (range, 0.25 to 240) months and 12 (range, 0 to 242) months, respectively. Median delays from onset of symptoms to RA diagnosis and treatment with csDMARDs were 15.7 (range, 2 to 252) months and 18 (range, 2 to 270) months, respectively. The mean number of consultations was 7.3±4.2 and the median number of physicians visited before the diagnosis was three (range, 1 to 8). The RA diagnosis delay was associated with rural geographic environment (p=0.02), lack of social insurance (p=0.027), progressive symptoms onset (p=0.006), morning stiffness (p=0.023), being initially examined by a GP (p=0.02), number of consultations (p<0.001; r=0.49), and number of physicians consulted before diagnosis (p=0.001; r=0.33) respectively. Based on the patients’ self-perception, the main causes of this long delay were lack of financial means (33%), wait times until exploration results (31%), wait times until the first GP or rheumatologist visit (26%), and geographical difficulty in accessing healthcare services (18%). Conclusion: Our study results suggest that patients with RA experience a significant delay until diagnosis and initiation of treatment. Healthcare providers should urgently consider factors related to diagnosis delay to shorten RA patients’ journey.